Detection of CD4+ and CD8+ lymphocytes in the intestine of broiler chicks treated with lactobacillus spp. and challenged with Salmonella enterica serovar enteritidis - Noujaim, J. C. [UNESP]; Andreatti Filho, Raphael Lucio [UNESP]; Lima, E. T. de [UNESP]; Okamoto, Adriano Sakai [UNESP] (Facta-fundacio Arnco Ciência Tecnologia Avicolas, 2009)
The expression of immune response as a leukocytic infiltrate by CD4+ and CD8+ cells in the epithelium and in the intestinal lamina propria of chicks fed Lactobacillus spp or cecal microflora (CM) and experimentally challenged or not with Salmonella enterica serovar Enteritidis (SE) was studied using immunohistochemistry. Three hundred and twenty day-of-hatch broiler chicks were divided into four groups of 80 birds each and orally received L. reuteri, L. salivarius, L. acidophilus, or CM. Each group was subdivided into four subgroups of 20 birds each, classified as follows: a subgroup did not receive any oral treatment (negative control), subgroup treated with L. spp or CM, subgroup treated with L. spp or CM and challenged with SE, and subgroup only challenged with SE (positive control). The results show that the oral treatment with L. reuteri, L. salivarius, L. acidophilus, or CM and challenge or not with SE stimulated bird immune response as determined by the leukocytic infiltrate by CD8+ lymphocytes followed by CD4+ in the epithelium and in the lamina propria of the duodenum, jejunum, and cecum of chicks up to 12 days of age. CD8+ lymphocyte number was significantly higher in the intestine of chicks receiving CM and challenged with SE. The duodenum, followed by the jejunum, were the segments in which the immune response, as shown by T, CD4+ and CD8+ cells, was stimulated with the greatest intensity.
Keywords: Chicken; Immunohistochemistry; Lymphocytes CD4+ and CD8+; Probiotic; Salmonella; Aves; Lactobacillus; Lactobacillus acidophilus; Lactobacillus reuteri; Lactobacillus salivarius; Salmonella enterica; Salmonella enteritidis